2021
DOI: 10.1126/science.abg0928
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ancestry effects on the response to viral infection are pervasive but cell type specific

Abstract: Ancestry shapes genetic immune responses Selection for genes affecting the immune system can vary among populations because of selection for local environments. In humans, ancestry has been associated with different responses to infection. Randolph et al . examined the molecular determinants of these observations using single-cell RNA sequencing of immune cells from individuals of European and African descent who were infected with influenza in vitro. The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
131
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(140 citation statements)
references
References 64 publications
9
131
0
Order By: Relevance
“…Generation of induced pluripotent stem cells (iPSC) may allow for the study of gene regulation across developing tissues or differentiated cells within diverse populations [68, 69], but such approaches remain technically difficult. This study is also restricted to steady state gene expression, which may miss cell-type- or dynamic, environment-specific genetic effects, which cannot be captured in bulk and/or steady-state tissues [29,70,14,13,71,72]. Despite these limitations, this study makes important contributions to our understanding of gene expression variation and the molecular basis of human adaptation in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of induced pluripotent stem cells (iPSC) may allow for the study of gene regulation across developing tissues or differentiated cells within diverse populations [68, 69], but such approaches remain technically difficult. This study is also restricted to steady state gene expression, which may miss cell-type- or dynamic, environment-specific genetic effects, which cannot be captured in bulk and/or steady-state tissues [29,70,14,13,71,72]. Despite these limitations, this study makes important contributions to our understanding of gene expression variation and the molecular basis of human adaptation in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Humans differ in their susceptibility to infectious disease due, in part, to variation in the immune response [ 81 ]. Immune pathway genes activated in response to influenza partly overlap those triggered by other single-stranded RNA viruses including COVID-19 [ 82 , 83 , 84 ]. These immune responses also vary by ancestry and stress the key role played by genetics in shaping population differences in immune responses [ 81 , 83 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immune pathway genes activated in response to influenza partly overlap those triggered by other single-stranded RNA viruses including COVID-19 [ 82 , 83 , 84 ]. These immune responses also vary by ancestry and stress the key role played by genetics in shaping population differences in immune responses [ 81 , 83 , 85 ]. In the current study, we confirmed many of the previously reported COVID–SNP and pneumonia–SNP associations [ 11 , 12 , 20 , 21 , 22 , 24 , 25 ], but none of these variants modified associations between COVID/pneumonia and dietary behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, scRNA-seq was also used to identify the effects of genetic ancestry on susceptibility to viral infection among individuals of European and African descent [ 12 ]. The authors used PBMCs from 90 donors that were either non-infected or infected with influenza A virus (IAV).…”
Section: Literature Reviewmentioning
confidence: 99%
“…eQTL analysis using scRNA-seq is a relatively new approach and only a dozen studies are available [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. These studies show diverse applications of scRNA-seq in identification of the quantitative effects of genetic variants or loci using purified cell types [ 4 , 5 ], induced pluripotent stem cells (iPSCs) [ 6 , 9 , 11 , 13 ] or whole organisms [ 10 ] and to study population ancestry and cell type specific response to an environmental stimulus such as viral infection [ 12 ]. In the following sections, we review the published sc-studies for of cis- eQTL analysis, and compare the results to bulk RNA-Seq based analysis ( Figure 1 ; Table 1 ).…”
Section: Introductionmentioning
confidence: 99%